FACIOBRACHIAL DYSTONIC SEIZURES: TWO CASES ALIKE, BUT NOT THE SAME. Issue 11 (9th October 2013) - Visser, Elizabeth; Duncan, Callum; Reid, John
Abstract : Background: The clinical entity of faciobrachial dystonic seizures (FBDS) related to positive voltage gated potassium channel antibodies (VGKC Lgi1) has been well documented. 1–3 Although described as seizures, as some cases have impaired consciousness associated with the dystonic movements. However the electroencephalogram (EEG) can be normal and patients respond poorly to antiepileptic medication. Instead, immunotherapy is advised to prevent progression to limbic encephalitis (LE), temporal lobe atrophy and cognitive impairment. 1 The dystonic movements implicate basal ganglia involvement. 4 Aims: We describe two male patients with FBDS. We wish to raise awareness of this condition as prompt management is required. Case 1: A 60 year old male presented with a first seizure, focal in onset on the left with secondary generalisation. A Computer tomography (CT) head scan showed small vessel ischemic change and the EEG was normal. He was started on antiepileptic treatment. Two weeks later he presented with cognitive difficulties, multiple stereotyped episodes of staring and dystonic posturing of his head, neck and left arm. Magnetic resonance imaging (MRI) brain showed scattered foci of high signal change in both hemispheres on T2, likely vascular in nature. Medial temporal structures were normal. High signal change was seen in the anterior half of the right putamen (Figure 1). EEG recorded the events but showed no epileptic changes. (Video of EEG). VGKC antibodies were positive 1422 pM (normal range 1–100). Other autoimmune screen, infection screen, CSF analysis and routine bloods were normal. Anti–epileptic treatment was ineffective. He remains on steroids and has minor cognitive difficulties. Case 2: A 58 year old male presented with brief stereotyped episodes of neck hyperextension and pronation, involving mostly the left and occasionally the right arm. Associated new cognitive difficulties were described. CT head showed minor lacunar ischemic change and routine bloods were normal. Serum Borellia serology was positive. CSF analysis was normal with no indication of active Borellia (CSF IgM negative and IgG positive). MRI brain showed minor small vessel changes. EEG showed irregular frontotemporal change, but no attacks were recorded and no epileptic changes seen. VGKC antibodies were positive 1069pM. He was treated with Ceftriaxone however the positive Borellia serology is likely to be incidental. Despite spontaneous termination of the FBDS, he was treated with steroids. His cognitive dysfunction remain mild. Conclusion: Our cases emphasise the different clinical features, different imaging features and EEG's seen with this condition and we hope to raise awareness of the importance of early clinical recognition, investigation and appropriate immunosuppresion.